KEBUTUHAN MEDIA PEMBELAJARAN MENULIS TEKS PROSEDUR PADA KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI SMA PEKANBARU - Setiawan, Fajar; Muhammad Mukhlis (Inspiratif Pendidikan, 2026)
Abstract: This study aims to identify the learning media needs for writing procedural texts with a deep learning approach at SMA Negeri 3 Siak Hulu and to determine how these learning media can support the stages of understanding, applying, and reflecting in learning to write procedural texts. This study uses a qualitative approach with a qualitative descriptive method. Data collection techniques were carried out through interviews, documentation, and observation, while data analysis techniques used the interactive analysis model according to Miles and Huberman. The results showed that the required learning media are visual media in the form of PowerPoint, serial images, infographics, flowcharts, and examples of procedural texts, as well as audio-visual media in the form of video tutorials and demonstration videos that can be paused to support the understanding and applying stages. Students still experience difficulties in the reflecting stage in composing imperative sentences, using verbs, and applying language rules. Obstacles found include technical problems, poor media quality, poor internet connection, limited device ownership, and lack of student focus. Solutions implemented include using printed media as an alternative, downloading videos before learning, utilizing real objects around, combining media with discussion and direct practice, and providing more intensive guidance and writing practice.